SDS-induced hexameric oligomerization of myotoxin-II from Bothrops asper assessed by sedimentation velocity and nuclear magnetic resonance - Henrickson, Amy (2023)
We report the solution behavior, oligomerization state, and structural details of myotoxin-II purified from the venom of Bothrops asper in the presence and absence of sodium dodecyl sulfate (SDS) and multiple lipids, as examined by analytical ultracentrifugation and nuclear magnetic resonance. Molecular functional and structural details of the myotoxic mechanism of group II Lys-49 phospholipase A2 homologues have been only partially elucidated so far, and conflicting observations have been reported in the literature regarding the monomeric vs. oligomeric state of these toxins in solution. We observed the formation of a stable and discrete, hexameric form of myotoxin-II, but only in the presence of small amounts of SDS. In SDS-free medium, myotoxin-II was insensitive to mass action and remained monomeric at all concentrations examined (up to 3 mg/ml, 218.2 μM). At SDS concentrations above the critical micelle concentration, only dimers and trimers were observed, and at intermediate SDS concentrations, aggregates larger than hexamers were observed. We found that the amount of SDS required to form a stable hexamer varies with protein concentration, suggesting the need for a precise stoichiometry of free SDS molecules. The discovery of a stable hexameric species in the presence of a phospholipid mimetic suggests a possible physiological role for this oligomeric form, and may shed light on the poorly understood membrane-disrupting mechanism of this myotoxic protein class.